NGHIÊN CỨU CHẾ TẠO VẬT LIỆU COMPOZIT TRÊN CƠ SỞ POLYPROPYLEN VÀ TRO BAY Ở TRẠNG THÁI NÓNG CHẢY - Hoàng, Thái; Giang, Nguyễn Vũ; Chinh, Nguyễn Thúy (Vietnam Journal of Science and Technology, 2012)
STUDY ON PREPARATION OF COMPOSITE MATERIALS BASED ON POLYPROPYLENE AND FLY ASH IN MELT STATE The composites of polypropylene (PP) reinforced by fly ash (FA)were prepared by melt mixing at 180°C in a Haake Rheomixer. Vinyl trimethoxy silane (VTMS) was used to modify FA and improve the interaction between PP and FA. The effect of FA contents on some characteristics such as relative melt viscosity, mechanical properties, and morphology of the composites has been investigated. The obtained results indicated that the relative melt viscosity of the composites PP/FA was decreased with increasing FA contents in PP. The tensile strength and elongation at break of the composites PP/FA with different content of FA were lower than those of neat PP. After modifying FA with VTMS (MFA), the composites PP/MFA exhibited higher tensile strength, and elongation at break, but lower relative melt viscosity than the composites PP/FA without VTMS (OFA) and PP/OFA/MFA. The comparison of above properties of the composites reinforced with MFA, OFA and mixed OFA and MFA revealed that the composites using MFA showed better reinforcing properties. Among the composites with MFA different content, the composite with 10% MFA showed the highest tensile strength and elongation at break. The SEM study of the cross surfaces of the composites indicated that the modification of FA  with VTMS increased interfacial interaction and adhesion  between PP and FA and also improved the dispersion ability of FA in PP matrix.